2018
DOI: 10.1111/obes.12226
|View full text |Cite
|
Sign up to set email alerts
|

The Labour Market Effects of Increases in Social Insurance Premium: Evidence from Japan

Abstract: Exploiting heterogeneous variations in labour cost increases due to Japan's 2003 social insurance premium reform as a natural experiment, we estimate the impacts of the increased social insurance premiums on employment, working hours and payroll costs. Using the difference‐in‐differences method with establishment fixed effects, we find that firms reduce the number of employees and increase average annual earnings from longer working hours in response to an exogenous increase in labour costs without productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Although not definitive because of data limitations (aggregate analysis, gap in the definition, and coverage of non-regular workers), results suggest that firms do not adjust the pay or work hours of part-time workers to avoid dismissals; rather, they dismiss part-time workers first during recessions and let the remaining full-time workers work longer than before so as to compensate for the dismissals of part-time workers. Indeed, this countercyclical movement of working hours among full-time workers is found in many existing studies on Japan (Kuroda and Yamamoto 2013;Genda, Kuroda, and Ohta 2015;Kodama and Yokoyama 2018). Note that these asymmetric wage and hour adjustments for full-and part-time workers are consistent with a hypothesis that firms hoard full-time workers during economic downturns.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Although not definitive because of data limitations (aggregate analysis, gap in the definition, and coverage of non-regular workers), results suggest that firms do not adjust the pay or work hours of part-time workers to avoid dismissals; rather, they dismiss part-time workers first during recessions and let the remaining full-time workers work longer than before so as to compensate for the dismissals of part-time workers. Indeed, this countercyclical movement of working hours among full-time workers is found in many existing studies on Japan (Kuroda and Yamamoto 2013;Genda, Kuroda, and Ohta 2015;Kodama and Yokoyama 2018). Note that these asymmetric wage and hour adjustments for full-and part-time workers are consistent with a hypothesis that firms hoard full-time workers during economic downturns.…”
supporting
confidence: 66%
“…Full-time workers in exporting firms work longer hours when their firms experience a negative shock in response to an appreciation. This countercyclical adjustment might seem counterintuitive at first glance, but many studies on Japan have found that work hours for remaining workers increase in response to massive dismissals during recessions (Kuroda and Yamamoto 2013; Genda et al 2015; Kodama and Yokoyama 2018). Note that the remaining workers are likely to be full-time workers and dismissed workers are likely to be part-time workers.…”
Section: Mechanismmentioning
confidence: 99%
“…The implementation of the SI Law has led to a noticeable increase in both the effective rate of social insurance contribution and participation. Consequently, as the primary contributors to social insurance premiums, enterprises have encountered a rise in labor costs (Kodama & Yokayama, 2015).…”
Section: Institutional Background and Theoretical Mechanismmentioning
confidence: 99%
“…First, social insurance contributions constitute a significant aspect of labor costs for enterprises, the current study examines whether social insurance contributions have “crowding‐out effect” on the labor force. Studies of microdata in Japan (Iturbe‐Ormaetxe, 2015; Kodama & Yokoyama, 2015) and Colombia (Kugler & Kugler, 2009) found that firms mitigate labor cost pressures by downsizing their workforce. In contrast, social insurance contributions decrease the relative cost of capital compared to labor, and enterprises may replace labor with capital investment to mitigate the escalating cost of labor, representing a “substitution effect.” Rising labor costs change the relative costs of firms' capital and labor (Broadberry & Gupta, 2006) and increase firms' use of advanced technology, machinery, and equipment, firms may replace labor with machines (Agrawal & Matsa, 2013; Serfling, 2016) to reduce the labor cost burden.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, government officials sought alternative revenue sources to support their expanded spending. Various studies and public reports highlighted a sharp increase in SSC in the post-2000 period (Chopel, Kuno, and Steinmo 2005, 28–29; Kodama and Yokoyama 2018, 993; Tax Commission 2007, 4). The VAT rate also increased in a phased manner in order to compensate for revenue losses driven by capital tax cuts (Brownlee and Ide 2017, 68–74; De Mooij and Saito 2014, 30; Ide and Steinmo 2009).…”
Section: Empirical Evidencementioning
confidence: 99%